Samurai I Mushashi Miyamoto - Takimura, Kazuo; Inagaki, Hiroshi ([S.l.] : Criterion Collection)
With his closest friend, Matahachi, Takezo (the town's wild, orphan kid) leaves his village to join an army on its way to battle. After their side loses, they seek shelter in the isolated home of a widow, Oko, and her daughter, Akemi. Oko seduces Matahachi, who forgets his betrothal to the virtuous Otsu. Oko, Matahachi, and Akemi go to Kyoto, but Takezo returns to the village. Matahachi's family rejects Takezo's report and has him arrested for treason. A monk rescues him from death and sentences him to the study of the samurai code. Otsu and Takezo fall in love, and she promises to wait him when he sets off on the road as a knight errant.
Executive producer, Hiroshi Inagoki
Cast: Rentaro Mikuni, Mariko Okada, Kuroemon Onoe, Akihiko Harata, Sojin Kamiyama
Keywords: Samurai films